Comparative analysis of different stroke subtype burden and future trends over 15 years in China and globally from 1990 to 2021 - Zeyan Zhang; Zeyan Zhang; Sijia Wu; Tianyu Jin; Zhixuan Duan; Zhixuan Duan; Xiaoxia Du; Xiaoxia Du (Frontiers in Neurology)
ObjectiveThis study aimed to characterize the temporal trends in the burden of various stroke subtypes, including incidence, prevalence, mortality, and disability-adjusted life years (DALYs), across different age and sex groups in China from 1990 to 2021 and compare these trends with global data.MethodsThis study utilizes data from the Global Burden of Disease (GBD) 2021 public dataset to examine temporal trends in different stroke subtypes over the past three decades, both globally and in China. Joinpoint regression and autoregressive integrated moving average (ARIMA) models were applied to analyze historical patterns and forecast future trajectories.ResultsThe age-standardized incidence rate (ASIR) and the age-standardized prevalence rate (ASPR) exhibited similar trends, with ischemic stroke (IS) showing an increase, while intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH) displayed a decline. The ASIR of IS in China increased from 100.049 to 135.789 per 100,000. In contrast, the ASIR for ICH decreased from 108.931 to 61.153 per 100,000, and the ASIR for SAH declined from 17.957 to 7.811 per 100,000. In terms of mortality and DLAYs, the age-standardized mortality rate (ASMR) and the age-standardized DALYs (ASDR) for IS, ICH, and SAH all declined. Globally, stroke burden decreased for all subtypes, with men generally more affected than women. The highest burden remains in older populations. Projections suggest a continued rise in IS and ICH prevalence, but a stable trend for SAH.ConclusionIn China, although the burden of most stroke subtypes has declined, IS and ICH still require sustained prevention and management efforts, particularly in light of their rising prevalence among men and the older adult.